Xq22.3-q23 deletion including ACSL4 in a patient with intellectual disability - Gazou, Anastasia; Riess, Angelika; Grasshoff, Ute; Schäferhoff, Karin; Bonin, Michael; Jauch, Anna; Riess, Olaf; Tzschach, Andreas (American journal of medical genetics, 2013)
Mutations or deletions of ACSL4 (FACL4, OMIM 300157) are a rare cause of non-syndromic X-linked intellectual disability. We report on a 10-year-old male patient with moderate intellectual disability, sensorineural hearing loss, facial dysmorphism, pyloric stenosis, and intestinal obstruction in whom a de novo Xq22.3-q23 deletion was detected by SNP array analysis. The deleted 1.56 Mb interval harbored ACSL4 and eight neighboring genes (GUCY2F, NXT2, KCNE1L, TMEM164, MIR3978, AMMECR1, SNORD96B, and RGAG1). In contrast to previously reported patients with chromosome aberrations in the region of the AMME complex (Alport syndrome, intellectual disability, midface hypoplasia, and elliptocytosis, OMIM 300194), this deletion did not contain the Alport syndrome gene COL4A5, suggesting that loss of one or several of the other genes in this interval is responsible for the clinical problems. In summary, the patient reported here broadens our knowledge of the phenotypic consequences of deletions of chromosome region Xq22.3-q23 and provides further proof for ACSL4 as an X-linked intellectual disability gene. © 2013 Wiley Periodicals, Inc.
Gesehen am 11.03.2021